Countering Radicalism in STEM: Design and Validation of the Tarbiyah Mentoring System Model for Mathematics Students - Nurhilaliyah, Nurhilaliyah; Rahman, Amri; Suwahyu, Irwansyah; Anam, Muh. Yusril (FKIP Universitas Lampung, 2025)
Countering Radicalism in STEM: Design and Validation of the Tarbiyah Mentoring System Model for Mathematics Students. Objectives: This study aims to develop the Anti-Radicalism Tarbiyah Mentoring System Model (TMSM) as an innovative character-building model for students in the Mathematics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar (UNM). The model is designed to strengthen students’ understanding, mentality, and moral attitudes in countering radicalism in the academic environment. Method: This research employed a Research and Development (R&D) approach using the PLOMP model, which consists of five stages. The study accomplished the first four stages: (1) needs assessment, (2) design, (3) realization, and (4) formative evaluation. Data were collected through surveys, focus group discussions (FGDs), and expert validation to ensure the feasibility, relevance, and quality of the developed instruments. Results: The study produced a prototype of the TMSM Anti-Radicalism (TAR) Model equipped with two supporting tools: the Training Implementation Plan (TIP) and the Weekly Training Pocket Book (WTPB). The mentoring-based training activities significantly contributed to enhancing students’ understanding, strengthening their mental resilience, and cultivating moral attitudes to develop an anti-radicalism character. Conclusion: The TMSM TAR Model can be applied as a structured, systematic, and sustainable mentoring framework to prevent radical tendencies among university students. However, further empirical testing is required to validate its effectiveness and adaptability in broader academic contexts, ensuring the sustainable implementation and long-term impact of the TMSM anti-radicalism (TAR) model. Keywords: development, anti-radicalism, TMSM model, character building.